Welfare-enhancing Trade Unions in an Oligopoly with Excessive Entry - Marco De Pinto; Laszlo Goerke (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
If input markets are competitive and output per firm declines with the number of firms (business stealing effect), there will be excessive entry into a Cournot oligopoly for a homogeneous commodity. However, input markets are often imperfectly competitive and the price of labor is determined by collective bargaining. The resulting rise in wages reduces output and profits and can deter entry. We analyze under which conditions greater bargaining power by the trade union reduces entry and raises welfare. Furthermore, we show that collective bargaining loosens the linkage between business stealing and excessive entry.
Keywords: D43; J51; L13; 330